INFLUENCE OF ISLAMIC LEADERSHIP AND ORGANIZATIONAL CULTURE ISLAMIC ON EMPLOYEES PERFORMANCE OF BANK SYARIAH INDONESIA (BSI) BINJAI BRANCH OFFICE - Abi Waqqosh; Riski Aseandi; Endri Dores; Yudistira Abdi (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine how the influence of Islamic leadership and Islamic organizational culture on the performance of employees of Bank Syariah Indonesia KC Binjai. The research uses quantitative methods with multiple linear regression analysis through the SPSS program as an intermediary. The results showed that simultaneously Islamic Leadership and Islamic Organizational Culture had a positive and significant influence on the performance of BSI KC Binjai employees. While partially, only Islamic leadership has a positive and significant influence, Islamic organizational culture does not have a positive and significant influence on employee performance. In this model Islamic leadership and Islamic organizational culture can only explain employee performance by 54.9%, the rest is explained by other variables not included in this research model.